Pola Interaksi Sosial Kelompok Islam dalam Sejarah Konsensus Dasar Negara Indonesia - Didik, Didik Hariyanto; Athoillah, Athoillah Islamy (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
This study aims to identify patterns of social interaction and the basis of argumentation of Islamic groups in the history of the consensus formulation of the primary state of Indonesia. This literature research uses a normative-historical approach. Associative and dissosiative intercation patterns become theories of analysis. The results showed that the pattern of social interaction of Islamic groups in the history of the consesus of the basic formulation of the Indonesian state used associative interaction patterns in the form of compromising attitudes towards nationalist groups. There are five big reasons for the compromise to be considered. First, the threat of disintegration from the representatives of Eastern Indonesia if the seven words in the state basis and the Islamic clauses of the Constitution are passed. Second, Indonesia's condition at that time experienced a power vacuum, becoming a momentum toward independence. Third, the promise of the secular nationalist group, after independence, a special meeting will be held to discuss the basis of the state and the constitution. Fourth, General Election discourse six months after Indonesia's independence, if it wins, it is hoped there will be an Islamic constitution. Fifth, the replacement of the sentence